Analisis Pengaruh Total Asset Turnover Terhadap Harga Saham Pada PT Kabelindo Murni Tbk - Adinda Putri Dwi Olsa; Muhamad Rimawan; Alwi Alwi (STIKes Ibnu Sina Ajibarang, 2024)
The aim of the research is to identify the influence of Total Asset Turnover (TATO) on share prices at PT Kabelindo Murni Tbk. The population used in this research is the financial reports at PT. Kabelindo Murni Tbk for 30 years (1992-2022). The sample in this research is financial report data for the last 10 years starting from 2013 to 2022 at PT. Kabelindo Murni Tbk. The sampling technique used is Non Probability Sampling, namely Purposive Sampling. The results of this research are that Total Asset Turnover has a significant effect on the share price of PT Kabelindo Murni Tbk with a significant value of 0.026 < 0.05.